The Effect of Youtube Media on Students' Understanding of Three-Dimensional Space in Elementary Schools - Putri, Firda Amelia; Ramadhany, Raudiyatus Zakiyah; Susilowati, Febi Arista; Amelia, Dewi Maisyafarotul; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
In mathematics learning, students often feel bored due to the monotonous media used. This article discusses the use of animated videos in teaching three-dimensional shapes. With animated videos, students find it easier to understand the material, and learning becomes more engaging. This study aims to facilitate the learning of three-dimensional shapes using animated videos as a learning medium. The research employs a quantitative method conducted at SDN Gunggung 1, involving 15 students, 1 teacher, and 1 student's guardian. The results of the study show that animated video media is effective in improving students' conceptual understanding in mathematics learning, including the topic of three-dimensional shapes. Animated videos can increase students' interest and motivation to learn. The roles of both teachers and students are crucial, especially in creating an engaging classroom atmosphere. The use of this medium makes it easier for teachers to teach and helps create an interactive and enjoyable learning environment.